2017
DOI: 10.1186/s13012-017-0545-4
|View full text |Cite
|
Sign up to set email alerts
|

Does access to a demand-led evidence briefing service improve uptake and use of research evidence by health service commissioners? A controlled before and after study

Abstract: BackgroundThe Health and Social Care Act mandated research use as a core consideration of health service commissioning arrangements in England. We undertook a controlled before and after study to evaluate whether access to a demand-led evidence briefing service improved the use of research evidence by commissioners compared with less intensive and less targeted alternatives.MethodsNine Clinical Commissioning Groups (CCGs) in the North of England received one of three interventions: (A) access to an evidence br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 40 publications
(35 reference statements)
2
16
0
Order By: Relevance
“…Paying consultants to synthesise evidence appears to be relatively common amongst our sample, but this may not be the case elsewhere (although some government agencies internationally have trialled or implemented into routine practice the establishment of partnerships with researchers that include evidence review/briefing services, e.g. [35, 53, 54]). Our findings show that access to consultants was a unique predictor of the number and types of research accessed, the extent to which evidence was appraised for relevance and quality and interactions with researchers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Paying consultants to synthesise evidence appears to be relatively common amongst our sample, but this may not be the case elsewhere (although some government agencies internationally have trialled or implemented into routine practice the establishment of partnerships with researchers that include evidence review/briefing services, e.g. [35, 53, 54]). Our findings show that access to consultants was a unique predictor of the number and types of research accessed, the extent to which evidence was appraised for relevance and quality and interactions with researchers.…”
Section: Discussionmentioning
confidence: 99%
“…This accords with a body of research which suggests that access to evidence alone is not sufficient to increase the use of research in policy. For example, Wilson et al concluded that receiving on-demand access to an evidence briefing service amongst six NHS Clinical Commissioning Groups in England [35] did not result in significantly increased intentions to use research evidence in their work, while Van Egmond’s depiction of the multifaceted, carefully constructed system the Centre VTV has developed in order to produce policy-relevant evidence for the Dutch government suggests that the process of providing useable evidence to policy may extend far beyond simply synthesising the available evidence [54].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We repeated the search in July 2018 using combination of index terms from the retrieved articles and reviews to identify new or updated research in MEDLINE ® , Google Scholar, and Scopus ® . 10,[38][39][40][41][42][43]…”
Section: Needs Assessmentmentioning
confidence: 99%
“…Tableau is preferred for high-dimensional reports, allowing for reporting across categories and comparing effectiveness of interventions using customized visualization formats. [40][41][42]…”
Section: Dissemination Product Two: Tableaumentioning
confidence: 99%